Forsøg med Centrifuger. Efter Foredrag i det kgl. Landhusholdningsselskab d. 24de Oktbr. - Fjord, N. J. (Tidsskrift for Landøkonomi, 2018)
Forsøg med Centrifuger. Efter Foredrag i det kgl. Landhusholdningsselskab d. 24de Oktbr.